Control of Growth and Differentiation by Drosophila RasGAP, a Homolog of p120 Ras–GTPase-Activating Protein - Feldmann, Pascale (American Society for Microbiology, 1999)
Mammalian Ras GTPase-activating protein (GAP), p120 Ras-GAP, has been implicated as both a downregulator and effector of Ras proteins, but its precise role in Ras-mediated signal transduction pathways is unclear. To begin a genetic analysis of the role of p120 Ras-GAP we identified a homolog from the fruit fly Drosophila melanogaster through its ability to complement the sterility of a Schizosaccharomyces pombe (fission yeast) gap1 mutant strain. Like its mammalian homolog, Drosophila RasGAP stimulated the intrinsic GTPase activity of normal mammalian H-Ras but not that of the oncogenic Val12 mutant. RasGAP was tyrosine phosphorylated in embryos and its Src homology 2 (SH2) domains could bind in vitro to a small number of tyrosine-phosphorylated proteins expressed at various developmental stages. Ectopic expression of RasGAP in the wing imaginal disc reduced the size of the adult wing by up to 45% and suppressed ectopic wing vein formation caused by expression of activated forms of Breathless and Heartless, two Drosophila receptor tyrosine kinases of the fibroblast growth factor receptor family. The in vivo effects of RasGAP overexpression required intact SH2 domains, indicating that intracellular localization of RasGAP through SH2-phosphotyrosine interactions is important for its activity. These results show that RasGAP can function as an inhibitor of signaling pathways mediated by Ras and receptor tyrosine kinases in vivo. Genetic interactions, however, suggested a Ras-independent role for RasGAP in the regulation of growth. The system described here should enable genetic screens to be performed to identify regulators and effectors of p120 Ras-GAP.